การศึกษาสมรรถนะพยาบาลจักษุ โรงพยาบาลมหาวิทยาลัยของรัฐ - โศศิษฐา ไชยมนตรี (จุฬาลงกรณ์มหาวิทยาลัย, 2017)
The purpose of this research was to describe the ophthalmic nurse competency based on career ladder, government university hospitals, using EDFR technique. Participants were 19 eye experts including physicians, nursing administrators, advanced practice nurses, staff nurses and professor. The EDFR consisted of 3 steps. Step 1, all experts were asked to describe the functional competency of ophthalmic nurse, government university hospital. Step 2, study data were analyzed by using content analysis to search for theme involving competency. Then those themes were developed for the study questionnaire. All items in the questionnaire were ranked the level of competency by a prior panel of experts. Step 3, items were analyzed by using median and interquartile range and then a new questionnaire version was developed. The new questionnaire was sent to prior experts for confirmation of item ranking. Ranked items were analyzed again by using median and interquartile range to summarize competency.The major finding were as follows: The ophthalmic nurse competency based on career ladder, government university hospital were classified in to 4 components: 1) Opthalmological nursing consisting of 100 sub – components. 2) Risk management consisting of 5 sub – component. 3) Providing information and counseling consisting of 15 sub - components. 4) Quality improvement consisting of 10 sub – components. The competency of nurses in each level has the same major competency but different detail as follows: 1) Nurse level 1 Provides nursig care and orther responsibilities at a basic level.Nurse level. 2) Provide specialized eye care and other responsibilities. In patients with no complex problems. 3) Nurse level 3 Applies advanced knowledge based on complicated eye patient and take team member role working with multidisciplinary team. 4) Nurse level 4 Solves any emergency problem rapidly and effective and be able to apply research to the practice.Nurse level. 5) Leads a nursing team to improve quality of nursing care via research and innovation and be able to be a good model in specialized eye nursing care.